Full factorial design‐of‐experiments for preparation of crosslinked dextran microspheres. Issue 5 (22nd May 2012) - Kenari, Hamed Salimi; Imani, Mohammad; Nodehi, Azizollah
Abstract This work describes full factorial design‐of‐experiment methodology for exploration of effective parameters on physical properties of dextran microspheres prepared via an inverse emulsion (W/O) technique. Microspheres were prepared by chemical crosslinking of dextran dissolved in internal phase of the emulsion using epichlorohydrin. The input parameters were dextran concentration in the aqueous phase, crosslinking ratio, and concentrations of sodium hydroxide and span 80 as the reaction catalyst and surfactant, respectively. Chemical structure of the resulting microspheres was analyzed spectroscopically using Fourier‐transform infrared technique. Final decomposition temperature, mean particle size and its distribution and equilibrium swelling ratio were selected as output responses. Microspheres with smooth surface were obtained according to scanning electron micrographs. It was found that an increase in dextran concentration in the aqueous internal phase increases mean particle diameter of the resulting microspheres, significantly. Moreover, water uptake capacity for the microspheres was dependent on both the dextran concentration and crosslinking ratio. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013